Pengaruh Variasi Radius Fillet Pada Poros Bertingkat Dengan Beban Gabungan Terhadap Faktor Keamanan - Wildan Rahmat Hafidzin; Oleh Oleh; Viktor Noubnome (Peneliti.net, 2023)
The shaft is the most important part of a transmission system that functions to continue rotation and mechanical power. In general, shafts are made in stages according to the conditions required. For each multilevel shaft section, radius fillets are always used. The purpose of this fillet is to reduce stress concentrations that occur due to changes in shaft diameter or other geometry. The constraints that arise are how large the size of the fillet must be used and what if the load that occurs is a combination of bending and twisting. From the results of research using the Ansys 14.5 application, it shows that a larger fillet size can distribute the maximum stress that occurs in that area. At a bending load of 250 N mm and a torsional load of 400 N mm with a fillet of 0.2 the maximum stress that occurs is 0.404 N/mm2. Whereas in fillet 0.12 the stress that occurs is 0.589 N/mm2.